Abnormal Doppler enteral prescription trial study: the results of a trial of feeding in a high risk group of premature babies. (16th November 2010) - Leaf, A; Dorling, J; Kempley, S; McCormick, K; Mannix, P; Brocklehurst, P
Abstract : Background: Abnormal antenatal Dopplers with intrauterine growth restriction (IUGR) are associated with increased adverse outcomes in premature infants. Anxiety about necrotising enterocolitis (NEC) often results in delay in enteral feeding. Babies of less than 35-week gestation with IUGR and abnormal antenatal Dopplers were randomised to early (24–48 h) or late (120–144 h) initiation of milk feeds, with protocol for increasing feed volume the same in both groups. Data collected included daily milk intake, evidence of gut pathology, sepsis and need for parenteral nutrition. Primary end points were days to full feeds (150 ml/kg/day) sustained for 3 days and NEC. Secondary end points included death, sepsis, growth and duration of parenteral nutrition and hospital stay.1 Results: 404 babies were randomised – 202 in each group. Data are presented on 372 completed outcome sets to date. Conclusion: Preterm infants with absent or reversed end-diastolic flow velocity on umbilical Doppler who were fed on Day 2 of life achieved full feeds earlier than those commenced on Day 6, with no difference in the incidence of NEC or sepsis.